2021
DOI: 10.48550/arxiv.2109.10580
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discs and outflows in the early phases of massive star formation: influence of magnetic fields and ambipolar diffusion

Benoît Commerçon,
Matthias González,
Raphaël Mignon-Risse
et al.

Abstract: Context. Massive star formation remains one of the most challenging problems in astrophysics, as illustrated by the fundamental issues of the radiative pressure barrier and the initial fragmentation. The wide variety of physical processes involved, in particular the protostellar radiative feedback, increases the complexity of massive star formation in comparison with its low-mass counterpart. Aims. We aim to study the details of mass accretion and ejection in the vicinity of massive star forming cores using hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 122 publications
0
3
0
Order By: Relevance
“…When non-ideal MHD, i.e. ambipolar diffusion, is included the scheme is the one described in Masson et al (2012) and used in previous studies (Masson et al 2016;Hennebelle et al 2020b;Mignon-Risse et al 2021;Commerçon et al 2021;Lebreuilly et al 2021). The resistivities are the ones calculated in Marchand et al (2016).…”
Section: Equations Numerical Methods and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…When non-ideal MHD, i.e. ambipolar diffusion, is included the scheme is the one described in Masson et al (2012) and used in previous studies (Masson et al 2016;Hennebelle et al 2020b;Mignon-Risse et al 2021;Commerçon et al 2021;Lebreuilly et al 2021). The resistivities are the ones calculated in Marchand et al (2016).…”
Section: Equations Numerical Methods and Setupmentioning
confidence: 99%
“…The simulations were performed with the adaptive mesh refinement (AMR) magnetohydrodynamics (MHD) code RAMSES (Teyssier 2002;Fromang et al 2006). When non-ideal MHD, namely, ambipolar diffusion, is included the scheme, as described in Masson et al (2012) and used in previous studies (Masson et al 2016;Hennebelle et al 2020b;Mignon-Risse et al 2021;Commerçon et al 2021;Lebreuilly et al 2021). The resistivities are the ones calculated in Marchand et al (2016).…”
Section: Equations Numerical Methods and Setupmentioning
confidence: 99%
“…In contrast, the influence of magnetic fields reduces disk formation due to magnetic braking as shown in Figure 8, which shows thin density projections of the dense circumstellar material, as a function of primary stellar mass, that surround the primary star along its equatorial plane for runs ROFµ φ 2 (top row) and ROFWµ φ 2 (bottom row). Rosen & Krumholz (2020) showed that magnetic braking, which removes angular momentum from the infalling material as the core collapses inhibits the formation of a discernible accretion disk around the massive star, however higher resolution and non-ideal MHD effects such as ambipolar diffusion and Ohmic re-sistivity may reduce how much angular momentum is removed leading to smaller accretion disks than those produced when magnetic fields are not included (e.g., Zhao et al 2020;Mignon-Risse et al 2021;Commerçon et al 2021). Such effects are not explored in this work.…”
Section: Accretion Disk Formation and Evolutionmentioning
confidence: 99%